The effects of migrant workers on the host country - Hasan, Sharina Farihah; Matsushima, Kakuya; Kobayashi, Kiyoshi (Thomas Telford Limited, 2009)
...This chapter aims to report on a study concerning migrant workers and their effects on the host country. The objective of the study is to investigate the effect of migrants on (i)the relative price and the wage rate, and (ii)the welfare of the native inhabitants in the host country. The methodology for the study involves a two-factors and two-sectors model developed to measure the effects......